Methionine Sulfoxide Reductases Contribute to Anaerobic Fermentative Metabolism in Bacillus cereus - Catherine Duport; Jean-Paul Madeira; Mahsa Farjad; Béatrice Alpha-Bazin; Jean Armengaud (MDPI AG, 2021)
Reversible oxidation of methionine to methionine sulfoxide (Met(O)) is a common posttranslational modification occurring on proteins in all organisms under oxic conditions. Protein-bound Met(O) is reduced by methionine sulfoxide reductases, which thus play a significant antioxidant role. The facultative anaerobe Bacillus cereus produces two methionine sulfoxide reductases: MsrA and MsrAB. MsrAB has been shown to play a crucial physiological role under oxic conditions, but little is known about the role of MsrA. Here, we examined the antioxidant role of both MsrAB and MrsA under fermentative anoxic conditions, which are generally reported to elicit little endogenous oxidant stress. We created single- and double-mutant Δmsr strains. Compared to the wild-type and ΔmsrAB mutant, single- (ΔmsrA) and double- (ΔmsrAΔmsrAB) mutants accumulated higher levels of Met(O) proteins, and their cellular and extracellular Met(O) proteomes were altered. The growth capacity and motility of mutant strains was limited, and their energy metabolism was altered. MsrA therefore appears to play a major physiological role compared to MsrAB, placing methionine sulfoxides at the center of the B. cereus antioxidant system under anoxic fermentative conditions.